Aesthetics and Criticism of Gending Sriwijaya Dance - Treny Hera; Agus Cahyono; Malarsi Malarsi; Eko Sugiarto (Universitas Negeri Semarang, 2023)
The focus of this study is the aesthetics of the Gending Sriwijaya dance in Palembang, South Sumatra. The aesthetics of Sriwijaya Gending are formed from dance choreography and a system of cultural values that grow and develop in the people of Palembang City. The choreography includes dance background, shape, form, theme, number and formation of dancers, movements, accompaniment, make-up, and clothing, as well as dance floor patterns. The cultural value system includes the source of the story that is communicated, the symbols that are expressed, and the function and meaning of dance for the supporting community. To approach this problem, Parker's conceptual reference is used, which emphasizes that aesthetics is beauty that attracts, touches, and thrills the soul because it is of value to us. Qualitative research methods, data collected through observation, interviews, and recording, as well as documentation studies. This study concludes that the Gending Sriwijaya choreography is based on ideas from folk legends in regencies and cities in South Sumatra and is combined with elements of Buddhist movements and Buddhist ascetic movements in the reliefs of Borobudur Temple. Therefore, the Gending Sriwijaya dance acts as a communication medium that instills ethical and moral values, while the cultural value system is very closely related to character education, including humility, trust, caring, harmony, patience, responsibility, sincerity, independence, and trust. self-loyalty and cooperation as education for the community and immigrant supporters.